Effect of rubber ball gripping range-of-motion exercise on hand muscle strength in patients with non-hemorrhagic stroke - Zainab Zainab; Ninik Yunitri; Rizki Nugraha Agung; Saharuddin Saharuddin (Lentera Perawat, 2026)
Background: Stroke remains a major cause of disability worldwide, often resulting in impaired upper limb function and decreased hand muscle strength that limit independence in daily activities. Simple, structured rehabilitation strategies such as range-of-motion (ROM) exercises using a rubber ball may provide practical and cost-effective support for motor recovery, yet evidence regarding their specific impact on hand muscle strength in non-hemorrhagic stroke patients remains limited. Objective: This study aimed to examine the effect of rubber ball gripping range-of-motion exercise on hand muscle strength in patients with non-hemorrhagic stroke. Methods: This study employed a pre-experimental one-group pretest–posttest design conducted in the Stroke Center inpatient ward of RSUD Labuang Baji Makassar. A total of 21 patients with non-hemorrhagic stroke who experienced upper extremity weakness were recruited using consecutive sampling based on predefined inclusion criteria. Hand muscle strength was measured using the manual muscle testing scale before intervention and daily after implementation. The intervention consisted of rubber ball gripping ROM exercise performed twice daily for six consecutive days as part of evidence-based nursing practice. Data were analyzed using descriptive statistics and paired statistical testing with a significance level of α = 0.05. Results: The mean hand muscle strength score increased from 3.10 ± 0.301 before intervention to 4.10 ± 0.301 after six days of exercise. Progressive improvement was observed beginning on the third day of intervention, with statistically significant differences between pre- and post-intervention measurements (p < 0.05). These findings indicate that repetitive ROM rubber ball gripping exercise contributed to clinically meaningful improvement in upper limb muscle strength among non-hemorrhagic stroke patients. Conclusion: Rubber ball gripping range-of-motion exercise demonstrated significant effectiveness in improving hand muscle strength in patients with non-hemorrhagic stroke.